Characterization and sensitivity to antibiotics of bacteria isolated from the lower respiratory tract of ventilated patients hospitalized in intensive care units - Manuel Medell; Mariana Medell; Alicia Martínez; Rodolfo Valdés (Brazilian Journal of Infectious Diseases, 2012)
Objectiv: Thisobservational study described the characterization of bacteria isolated from the lower respiratory tract of ventilated patients hospitalized in intensive care units. The demonstration of isolated microorganism resistance to antibiotics and a time-trend analysis of infection comparing a 48-month period were also other objectives. Method: Semi-quantitative assays of 1254 samples taken from 741 ventilated patients were performed, while pathogens were identified using the Enterotube II assay and VITEK 2 Compact equipment. Bacterial resistance to antibiotics was assessed by the Kirby-Bauer disc diffusion method and time-trend analysis of infection was based on data recorded by hospital microbiology laboratories. Results: The most prevalent isolated bacteria from the patient's lower respiratory tract were with Gram-negative bacteria (67.8%) mostly represented by: Acinetobacter spp. (25.2%), Pseudomonas spp. (18.3%) and Klebsiellas spp. (9.4%). Acinetobacter spp. showed moderate high to very high resistance to ceftriaxone (CRO), gentamicin (CN), amikacin (AK), meropenem (MRP), aztreonam (ATM) and piperacillin/tazobactam (TZP). Some isolates of Acinetobacter spp. resistant to colistin (CS) were identified in this patient population. Pseudomonas spp. and Klebsiella spp. were very highly resistant to ampicillin/sublactam (AMS) and with moderate or low resistance to CRO, ATM, MRP, AK, CN and TZP. A decrease in the Pseudomonas spp. prevalence rate was observed, whereas an increase in Acinetobacter spp. and Klebsiella spp. prevalence rates were observed in a 48-month period. Conclusion: This research corroborated that these nosocomial infections are a relevant medical problem in our context. The most prevalent bacterial infections in the lower respiratory tract of ventilated patients were by Acinetobacter spp., Pseudomonas spp. and Klebsiella spp. The panel of antibiotics used as preventive therapy was not the solution of infections and probably induced drug-resistance mechanisms in these isolated microorganisms. Keywords: Anti-bacterial agents, Respiratory care units, Bronchopneumonia